Reusability of L-asparaginase immobilized on silica-based supported ionic liquids - Nunes, João C. F. (2021)
L-asparaginase (ASNase) is an aminohydrolase enzyme used as an anticancer drug, e.g. in the treatment of acute lymphoblastic leukemia, in acrylamide reduction and in biosensing. Nevertheless, its low stability and thermolability, and susceptibility to proteases, hinder its application in the health and food industries. Hence, the improvement of its properties through efficient immobilization methods is in high demand. Thus, this work aims the development of silica-based supported ionic liquids (SILs) for the ASNase immobilization to improve its stability and enable its reusability. While activated silica with no ILs only kept total initial ASNase activity during the first cycle of reaction, SILs allowed 5 cycles of reaction, keeping 82% of initial ASNase activity, reinforcing their potential as alternative enzymatic supports.